Analysis Of Determinants Of Value Of Pharmaceutical Sub-Sector Companies Listed On The Indonesian Stock Exchange For The 2018-2022 Period - Kurniawati, Tri Ade; Marissa Natalia Pardede; Didik Gunawan; Willy Cahyadi (SEAN Institute, 2024)
The pharmaceutical industry is among the economic sectors that achieved positive growth, despite Indonesia facing a contraction in the second quarter of 2020. This growth is evident from several pharmaceutical companies listed on the Indonesia Stock Exchange, which saw an increase in profits in 2020.The aim of this research is to determine the value of pharmaceutical companies listed on the Indonesia Stock Exchange from 2018 to 2022. The growth of pharmaceutical companies in Indonesia is driven by the country's increasing population and government efforts to improve public health. Through the implementation of the National Health Insurance (JKN) program. This research uses a sample of 8 pharmaceutical companies listed on the Indonesian Stock Exchange. This research uses quantitative descriptive methodology and panel data regression techniques for research analysis. The research results show that the profitability of pharmaceutical subsector companies listed on the Indonesia Stock Exchange has a fairly large influence on overall company value. The existence of liquidity and capital structure does not affect the assessment of pharmaceutical subsector companies listed on the Indonesian Stock Exchange.